Physiological and Productive Role of Biostimulants in Alleviating Hypoxia Stress in Soybean Grown Under Field Conditions - de Andrade Silva, Ricardo; Lessa Silva, Wilton; Farias Damasceno, Lucas; Luís Oliveira Cunha, Matheus [UNESP]; Angelica Carvalho Mendes, Nandhara [UNESP]; Aparecido Manzani Lisboa, Lucas [UNESP] (Springer Nature, 2023)
Hypoxia can reduce cellular respiration, ATP synthesis and crop yield and increase production of reactive oxygen species. The use of biostimulants in agriculture has been growing considerably and its use is associated as a strategy to increase crop productivity and plant resistance against abiotic stress. This study aimed to verify the influence of the application of biostimulants on the development and yield of soybean crop grown under hypoxia under field conditions. The treatments were composed of different biostimulants, being the control (no application), Lysine, Tryptophan, Methionine, Betaine-glycine, Histidine, Arginine, Leucine, Aparagine, Alanine, Glutamic acid, Proline, Phenylamine, Serine, Valine, Amino acid extract and algae extract, applied via foliar in soybean cultivated under hypoxia totaling 17 treatments. Hypoxia significantly reduced chlorophyll concentration, number of branches, shoot fresh weight and yield of soybean plants. The use of serine, proline, valine, algae and, amino acid extracts, methionine, arginine and betaine-glycine is promising to increase soybean tolerance to hypoxia by improving physiological parameters, development and yield of plants. Our results contribute to increase knowledge about the influence of biostimulants in combating the stress caused by hypoxia in the soybean crop and can be used as a strategy in agriculture to increase food production in the face of climate change and population growth in order to guarantee food security.
Keywords: Abiotic stress; Chlorophyll; Plant height; Yield